The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/sla.0000000000005005
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Evaluating Electronic Outpatient Symptom Monitoring After Ambulatory Cancer Surgery

Abstract: Objective:We implemented routine daily electronic monitoring of patient-reported outcomes (PROs) for 10 days after discharge after ambulatory cancer surgery, with alerts to clinical staff for worrying symptoms. We sought to determine whether enhancing this monitoring by adding immediate automated normative feedback to patients regarding expected symptoms would further improve the patient experience.Summary of Background Data:PRO monitoring reduces symptom severity in cancer patients. In ambulatory cancer surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…23 Additionally, a trial randomizing ambulatory cancer surgery patients to daily PROMs vs enhanced PROMs with immediate normative feedback regarding expected symptoms significantly decreased nursing calls, which may offset some of the burden on clinical staff. 24 The prospective nature of this pilot mirrors realtime data collection during the 30-day home recovery phase after cystectomy. However, its small sample size limits quantitative correlation of clinical outcomes with symptoms scores and biometric phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Additionally, a trial randomizing ambulatory cancer surgery patients to daily PROMs vs enhanced PROMs with immediate normative feedback regarding expected symptoms significantly decreased nursing calls, which may offset some of the burden on clinical staff. 24 The prospective nature of this pilot mirrors realtime data collection during the 30-day home recovery phase after cystectomy. However, its small sample size limits quantitative correlation of clinical outcomes with symptoms scores and biometric phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…23 Additionally, a trial randomizing ambulatory cancer surgery patients to daily PROMs vs enhanced PROMs with immediate normative feedback regarding expected symptoms significantly decreased nursing calls, which may offset some of the burden on clinical staff. 24…”
Section: Discussionmentioning
confidence: 99%
“…The RCT reported by Pusic et al5 did not reject the null hypothesis that patients in the enhanced feedback group did not have different avoidable UCC visits compared with those in the team monitoring group. Although the between-group difference was not statistically significant, the enhanced feedback group tended to have more avoidable UCC visits (4.6% vs. 3.4%).…”
mentioning
confidence: 90%
“…It demonstrated that electronic symptom monitoring with intervention in response to alerts reduced potentially avoidable urgent care center (UCC) visits compared with the usual care, but increased the number of nursing calls 6. This RCT included a large sample size of 2624 patients undergoing ambulatory cancer surgery and revealed that providing patients with automated normative feedback regarding their symptom severity reduced patient anxiety and nursing calls compared with providing patients with remote symptom management via team monitoring, but the rates of UCC visits between the 2 groups were not significantly different 5…”
mentioning
confidence: 98%
See 1 more Smart Citation